2016
DOI: 10.1063/1.4941604
|View full text |Cite
|
Sign up to set email alerts
|

Internally contracted multireference coupled-cluster theory in a multistate framework

Abstract: The internally contracted multireference coupled cluster (icMRCC) theory is reexamined in a multistate framework. The new derivation starts from the Bloch equations employing a wave operator similar to the one originally employed by Jeziorski and Monkhorst [Phys. Rev. A 24, 1668 (1981)], but allows for a multideterminantal model-space basis. The resulting working equations are a generalization of state-universal multireference coupled-cluster (SU-MRCC) theory. In the case of truncated cluster operators, energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Another possibility to access excited states is the multistate version of the ic-MRCC method, which has been presented recently by Aoto and Köhn. 251 Not too much experience is available yet, but it is hoped that in this way it will be possible to describe state crossing (also with the ground state). Promising results have been presented for LiF and BeF.…”
Section: Multireference Coupled Cluster Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility to access excited states is the multistate version of the ic-MRCC method, which has been presented recently by Aoto and Köhn. 251 Not too much experience is available yet, but it is hoped that in this way it will be possible to describe state crossing (also with the ground state). Promising results have been presented for LiF and BeF.…”
Section: Multireference Coupled Cluster Methodsmentioning
confidence: 99%
“…Promising results have been presented for LiF and BeF. 251 The relation of pIC-MRCC to EOM-CC led to its straightforward generalization for multiple states. In the so-called MR-EOMCC method of Nooijen and coworkers, [252][253][254] instead of diagonalizing H in the MRCIS space as in pIC-MRCC, the space is now extended by the inclusion of up to double excitations into the active space.…”
Section: Multireference Coupled Cluster Methodsmentioning
confidence: 99%
“…Relaxing the reference coefficients is in fact one of the main reasons for the particular accuracy of the resulting method and it has been shown that it thus unifies state-specific and multistate coupled-cluster theories. 141 The success of the method comes at a price of high complexity of the underlying equations, in particular due to the non-commutativity of the cluster operator manifold. 138 The current Molpro implementation still relies on a symbolic code (called GeCCo) that is generated by the automatized evaluation of the underlying secondquantized operator algebra.…”
Section: Internally Contracted Multireference Coupled-clustermentioning
confidence: 99%
“…This unphysical behavior inherent of SA-CASSCF must be cured a posteriori by multistate variants of MRPT 4,8587 or MRCC. 88…”
Section: Introductionmentioning
confidence: 99%